1998
DOI: 10.1103/physrevlett.80.4265
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Image Potential at an Al(111) Surface

Abstract: We evaluate the electronic self-energy Σ(E) at an Al(111) surface using the GW space-time method. This self-energy automatically includes the image potential Vim not present in any local-density approximation for exchange and correlation. We solve the energy-dependent quasiparticle equations to obtain surface state wavefunctions, and calculate the effective local potential experienced by electrons in the near-surface region. We find that Vim for unoccupied states is due to correlation (not exchange). The image… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 26 publications
2
65
1
Order By: Relevance
“…Note that image-potential effects are an intrinsic feature of the GW (and GdW ) self-energy operator. 31,32 (ii) The QP correction of the LUMO changes sign as a function of its occupation n (referring to one spin channel, i.e., 0 < n < 1). If the state were empty (occupied) it would observe a GdW correction of GdW n=0 > 0 ( GdW n=1 < 0), as shown in Fig.…”
Section: (B) and 2(c) And Open Circles Inmentioning
confidence: 99%
“…Note that image-potential effects are an intrinsic feature of the GW (and GdW ) self-energy operator. 31,32 (ii) The QP correction of the LUMO changes sign as a function of its occupation n (referring to one spin channel, i.e., 0 < n < 1). If the state were empty (occupied) it would observe a GdW correction of GdW n=0 > 0 ( GdW n=1 < 0), as shown in Fig.…”
Section: (B) and 2(c) And Open Circles Inmentioning
confidence: 99%
“…The damping rate of an excited electron in the state 0 (r) with energy E is in fact obtained as 23 One recent GW application touching this point is the work of White et al (1998) on the image potential at the Al(111) surface.…”
Section: A Evaluation Of the Green's Function Gmentioning
confidence: 99%
“…(43). The combination of this capability with the pumpprobe techniques can give very detailed information about momentum-dependent relaxation and scattering processes at surfaces [3].…”
Section: Momentum Dependence Of Lifetimesmentioning
confidence: 99%
“…When the test charge is an electron it is necessary to take also into account exchange and correlation interactions. White et al [43] showed that for an electron trapped in an image-potential state the image potential is created by long-range correlation interactions. They did a self-energy calculation within the GW approximation [13] for very thin (five atomic layers) Al(1 1 1) films separated by a narrow (eight interlayer spacings) vacuum region.…”
Section: Introductionmentioning
confidence: 99%